2011
DOI: 10.1016/j.tsf.2011.05.062
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thermomechanical responses in ultrafast laser heating of metal nanofilms

Abstract: The present work uses two-temperature model and Cattaneo's constitutive model to study the thermomechanical responses and the size effect on energy transport during ultrafast laser heating of Au nanofilms. It is shown that the grain size effects on thermophysical properties, heat transport and thermal stresses are rather evident when the average grain diameter is less than the electron mean free path. The study on heat transport shows that there are two heat waves propagating in the lattice during nonequilibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Table 1: Physical properties of materials at 300 K. (Guo and Huo, 2010;Bergman et al, 2007;Cottrell, 1964). Concerning the two different laser pulses applied on the left boundary, one of them presents a Gaussian distribution function (Qiu and Tien, 1992;Tzou, 1995;Zhou and Ma, 2011;Wang et al, 2011;Zou et al, 2014), while the other one presents a Cosseinodal pulse function (Guo and Huo, 2010;Wang et al, 2010). These two functions are defined according to Eqs.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1: Physical properties of materials at 300 K. (Guo and Huo, 2010;Bergman et al, 2007;Cottrell, 1964). Concerning the two different laser pulses applied on the left boundary, one of them presents a Gaussian distribution function (Qiu and Tien, 1992;Tzou, 1995;Zhou and Ma, 2011;Wang et al, 2011;Zou et al, 2014), while the other one presents a Cosseinodal pulse function (Guo and Huo, 2010;Wang et al, 2010). These two functions are defined according to Eqs.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Its mathematical models are often called non-Fourier heat conduction models. Some studies have been performed using non-Fourier heat conduction models to analyze the heat conduction in metallic nanofilms heated by an ultrafast laser pulse (Zhou and Ma, 2011;Wang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that although the trends in the predicted maximum tensile stresses with respect to laser processing conditions were the same, the contours in the tensile stresses on the surfaces of the treated tracks were significantly different for two simulation cases, using thermal loads provided by different thermal models that either considered or neglected latent heat of fusion and fluid flow of the melt pool. Thermomechanical responses in ultrafast laser heating of metal nano-films were studied by Zhou and Ma [12]. They showed that the classical thermo-elastic theory could not reveal the generation of the ultrafast thermal stresses during non-equilibrium heating; however, it could approximately describe the stress evolution in the stage of thermal equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the experimental conditions, the donor material is melted and/or partially vaporized. Due to the thermally induced stresses [54,64] and the arising pressure due to a potential vapor bubble [36,41], the donor material is subsequently ejected and propelled towards the receiver, see figure 1.1. Volume, size and morphology of the deposited feature strongly depend on the processing parameters, as these determine the dominating physics triggering the ejection process.…”
Section: Laser-induced Forward Transfermentioning
confidence: 99%